The treatment landscape of advanced angiosarcoma in Asia—A multi‐national collaboration from the Asian Sarcoma Consortium. Issue 3 (7th February 2021) - Chen, Tom Wei‐Wu; Pang, Angela; Puhaindran, Mark E.; Maw, Myo Myint; Loong, Herbert H.; Sriuranpong, Virote; Chang, Chih‐Chi; Mingmalairak, Siyamol; Hirose, Takeshi; Endo, Makoto; Kawai, Akira; Farid, Mohamad; et al.
Abstract: Angiosarcoma (AS) is a rare disease with a dismal prognosis. The treatment landscape and prognostic factors for advanced AS, including locally advanced, unresectable, and metastatic disease remain elusive. The Asian Sarcoma Consortium is an international collaborative effort to understand the sarcoma treatment landscape in Asia. We undertook a retrospective chart review of AS patients seen in 8 sarcoma academic centers across Asia. Patients with complete clinical, treatment, and follow‐up data were enrolled. Overall, 276 advanced AS patients were included into this study; 84 (30%) of the patients had metachronous metastatic AS. The median age was 67 y; primary sites of AS was cutaneous in 55% and visceral in 45% of patients. In total, 143 (52%) patients received at least 1 line of systemic chemotherapy. The most common first‐line chemotherapy regimen used was paclitaxel (47.6%) followed by liposomal doxorubicin (19.6%). The median overall survival (OS) was 7.8 mo. Significant prognostic factors for OS included age > 65 (hazard ratio (HR) 1.54, P  = .006), male gender (HR 1.39, P  = .02), and a cutaneous primary AS site (HR 0.63, P  = .004). The median progression‐free survival (PFS) for first‐line chemotherapy was 3.4 mo. PFS for single vs combination or paclitaxel vs liposomal doxorubicin chemotherapy regimens were comparable. This study provides an insight into the treatment patterns and prognostic factors of advanced AS patients in Asia. Prognosis of advanced AS remains poor. Data from this study serve as a benchmark for future clinical study design. Abstract : With a total of 276 advanced angiosarcoma patients, we provided the complete clinicopathological demographics, treatment patterns, and prognostic outcomes of advanced angiosarcoma in Asia.